PARAMETER OPTIMIZATION OF PITCH CONTROLLER FOR ROBUST FREQUENCY CONTROL IN AN ISOLATED WIND-DIESEL HYBRID POWER SYSTEM USING GENETIC ALGORITHM - Cuk Supriyadi Ali Nandar (Universitas Ahmad Dahlan, 2008)
This paper focuses on the parameter optimization of the pitch controller for robust frequency control in an isolated wind-diesel hybrid power system. The structure of the pitch controller is a practical 1st–order lead-lag compensator. In system modeling, the normalized coprime factorization is applied to represent system uncertainties such as variations of system parameters etc. As a result, the robust stability of the controlled system against various uncertainties can be guaranteed. To obtain the controller parameters, the performance and stability conditions of H∞ loop shaping control are employed to formulate the optimization problem. The genetic algorithm is used to solve the problem. The frequency control effect and robustness of the proposed pitch controller against system uncertainties are evaluated by simulation studies in comparison with a variable structure pitch controller.